Lean Education Strategy in Optimizing Governance and Resilience Educational Institution Resources - Khomsinnudin, Khomsinnudin; Aminudin S, Muh. Dzihab; Sholikhah, Riyadlotu (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This study investigates the application of Lean Education strategies to optimize governance and resource resilience within Islamic higher education institutions in Indonesia. The primary objective is to examine how Lean principles such as waste elimination, efficiency improvement, and value creation can enhance operational performance and educational quality. A descriptive qualitative approach was employed using a multiple case study design across three private higher education institutions in Lampung: STIT Darul Ishlah Tulang Bawang, IAI Tulang Bawang, and STIES Darul Huda Mesuji. The research identified critical operational wastes (muda), including academic overproduction, administrative waiting times, and uncoordinated transportation inefficiencies. Crucially, this study highlights the unique integration of traditional Islamic boarding school (pesantren) values, such as barakah (blessing), ihsan (excellence), and istiqamah (consistency), into the Lean framework. The findings reveal that Lean Education can be effectively sustained through transformational hybrid leadership, cost-effective technology adoption, and dynamic, lived Standard Operating Procedures (SOPs). The proposed adaptive model demonstrated substantial empirical performance improvements, including a 45% reduction in academic process lead times and a 25% increase in value-added operational activities. This study provides valuable practical and theoretical insights for higher education administrators seeking to optimize resource management without compromising spiritual and institutional cultural identity.